The Wilson disease gene is a putative copper transporting P-type ATPase similar to the Menkes gene. - Bull, P; Thomas, G; Rommens, J; Forbes, JR; Cox, D (1993)
Wilson disease (WD) is an autosomal recessive disorder of copper transport, resulting in copper accumulation and toxicity to the liver and brain. The gene (WD) has been mapped to chromosome 13 q14.3. On yeast artificial chromosomes from this region we have identified a sequence, similar to that coding for the proposed copper binding regions of the putative ATPase gene (MNK) defective in Menkes disease. We show that this sequence forms part of a P-type ATPase gene (referred to here as Wc1) that is very similar to MNK, with six putative metal binding regions similar to those found in prokaryotic heavy metal transporters. The gene, expressed in liver and kidney, lies within a 300 kb region likely to include the WD locus. Two WD patients were found to be homozygous for a seven base deletion within the coding region of Wc1. Wc1 is proposed as the gene for WD.